(untitled) (Balneo and PRM Research Journal, 2024)
Abstract: Background: The prevalence of total knee arthroplasties (TKA) is rising, especially among younger patients due to sports-related injuries and early osteoarthritis onset. Post-operative outcomes in younger patients show promise, but current rehabilitation approaches lack specificity for this group. This study aims to evaluate a post-operative rehabilitation program tailored for younger TKA recipients.; Methods: Patients from a single arthroplasty center who underwent TKA were age and sex-matched into two groups: Group A with an advanced 12-week rehabilitation program and Group B with a standard rehabilitation program. Eligibility required participants to be under 60 and ready for a specific TKA type, with assessments at baseline and 12 weeks post-operative using the KSS, KOOS, and SF-36 scales. Results: At the 12-week follow-up, Group A, having received the advanced rehabilitation protocol, showed significantly higher KOOS (A: 85.1 ± 8.7 vs. B: 83.7 ± 11.1; p=0.042) and KSS (A: 82.9 ± 8.4 vs. B: 78.7 ± 9.2; p=0.020) scores than Group B. Both groups demonstrated marked improvements with an attendance rate of 88% (A) compared to 82% (B), although there was no significant difference in overall mean tolerability scores between the groups. Conclusions: Patients undergoing advanced rehabilitation after total knee arthroplasty showed significant improvements compared to standard protocols. Despite minor variations influenced by social determinants, the advanced protocol was more effective in post-operative recovery. Keywords: Advanced rehabilitation; total knee arthroplasty; post-operative recovery.